0782 Changes in markers of ventricular repolarization and positive airway pressure therapy: A pilot study. (25th May 2022) - Perez, Karolina; Zareba, Wojciech; LaFleur, Bonnie; Xia, Xiaojuan; Woosley, Raymond; Patel, Imran; Quan, Stuart; Grandner, Michael; Youngstedt, Shawn; Miller, Jerod; Parthasarathy, Sairam; Patel, Salma
Abstract: Introduction: Positive airway pressure (PAP) therapy is the mainstay treatment for obstructive sleep apnea (OSA). Continuous PAP (CPAP) therapy has been shown to decrease QTc length in electrocardiograms in patients with OSA in small studies. The impact of higher pressures of CPAP and Bilevel PAP (BPAP) on ventricular repolarization—QTc length and QT variability in OSA is unknown. The goal of this pilot study is to explore this relationship. Methods: 10 consecutive patients who underwent polysomnography during which they had a diagnostic, CPAP titration, and BPAP titration portion were included for analysis. Bazett's heart rate correction was used to calculate QTc. QT variability was measured as short-term interval QT variability (STVQT) and normalized QT interval variance (QTVN). All variables were analyzed for the entire duration of the diagnostic period, on the highest CPAP pressure and highest BPAP pressure delivered. Results: The patients were 49 ± 15 years of age and 60% women. Median CPAP pressure was 14.5 cm H2O (mean 13.5 ± 5 cm H2O). For BPAP, the median inspiratory PAP was 21.5 cm H2O (mean 20.5 ± 5 cm H2O) and EPAP median was 16 cm H2O (mean 15.9 ± 4 cm H2O). Mean QTc for the diagnostic portion, highest CPAP pressure and highest BPAP pressure were 430 ± 17 ms, 445 ± 15 ms and 441 ± 21 ms, respectively (p=0.141). Mean QTVN for the diagnostic portion, highest CPAP pressure and highest BPAP pressure settings were 0.0011 ± 0.0008 dimensionless units (du), 0.0012± 0.0008 du and 0.002 ± 0.0012 du, respectively (p=0.127). STVQT for the diagnostic portion, highest CPAP pressure and highest BPAP pressure settings were 6.62 ± 4.13 ms, 9.12 ± 4.7271 ms and 12.62 ± 4.99 ms, respectively (P=0.041). Post-hoc pairwise comparisons between BPAP and diagnostic portions of the study were significant for STVQT (P=0.034). Conclusion: Short-term QT variability, STVQT, was significantly increased on BPAP when compared to the diagnostic portion of the study. Support (If Any): American Academy of Sleep Medicine Foundation (203-JF-18), National Institutes of Health (HL126140, 2L30HL154400-023) University of Arizona Health Sciences Career Development Award (5299903), and University of Arizona Faculty Seed Grant (5833261)